Densities, Refractive Indices and Excess Properties of Binary Mixtures of Acetonitrile with Benzene, Toluene, m-Xylene and Mesitylene at Temperatures from (298.15 to 313.15) K - Shams, Abeer K (Al-Nahrain Journal of Science, 2011)
The densities (ρ) and refractive indices (nD) of binary mixtures of acetonitrile with benzene, toluene, m-xylene and mesitylene including those of pure liquids, over the entire composition range expressed by mole fraction x1 of acetonitrile were measured at temperatures (298.15, 303.15, 308.15, and 313.15) K under atmospheric pressure. From the experimental data, the excess molar volumes (VEm ) and the deviations in refractive indices (Δn) were calculated. These results are fit to a Redlich-Kister type polynomial equation. The results indicate the presence of weak interactions between acetonitrile and aromatic hydrocarbon molecules. The deviations in VEm values follow the order toluene < benzene < m-xylene < mesitylene. The results are discussed in terms of the intermolecular interactions.